Geometry, Biophysics and neuroscience. On the quantum nature of life and consciousness in the confluence of the thoughts of Erwin Schrödinger and Hermann Weyl - Béjar Gallego, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The new theoretical and experimental developments in neurosciences project an idea of consciouness deeply bound to the physical nature. Nevertheless, consciousness does enigmatically keep without scientific explanation. The phenomenum per se is commonly known, but its definition and position in the modern scientific frames are not well determined. Consequently, there are plenty different interpretations full of speculation and imagination. On the opposite side, the scientific consciousness research is not frequent and it is exclusively done by a reduced group of researchers that works on the psycho-physical connection between physical matter and its psychical emergent activity from the neuroscientific experimental data. In this paper we widely explain a fundamental contextualized synthesis of two scientific geniuses in the mind-matter relationship problem. Although they belong to a near past, Erwin Schrödinger and Hermann Weyl are both paradigmatic personalities because of their methodical rigor and widespread investigations, which characterize the strong scientific spirit. Their styles are stout, their works inspire future researches and their conclusions connect well with the last frontiers results in neurosciences and quantum physics.
Keywords: formalism-intuitionism; field-geometry; causality-indeterminism; biogenesis-conciousness; holism-quantum